Prevalência, distribuição espacial e fatores de risco para cisticercose bovina no estado de São Paulo - Ferreira, Marlon Martins; Revoredo, Thais Buranello; Ragazzi, Juliana Pistore; Soares, Vando Edésio; Ferraldo, Antônio Sérgio [UNESP]; de Mendonça, Rafael Paranhos; Lopes, Welber Daniel Zanetti (My University, 2014)
This study aimed to determine the prevalence and geographical distribution as well as the factors and areas of risk associated with bovine cysticercosis in the State of São Paulo. 34.443 cattle, males and females with ages from 18 to 60 months were inspected. The animals were from 97 cities in the state of São Paulo and identified and slaughtered in the period October 2010 to August 2011, in a refrigerator located in Ipuã - SP, under the supervision of SIF 1387. The state of São Paulo was divided into regional centers, and the data of the municipalities belonging to its core, were grouped according to the Department of Agriculture and Food Supply of São Paulo, totaling 13 cores studied. Based on these results, we can conclude that of the 97 cities analyzed, cattle were found positive for the disease in 86. The average prevalence of bovine cysticercosis in the state of São Paulo was 4.80 %, while the core inflation Franca and Barretos were the ones with the highest number of cases illness during the analysis period. Moreover, the largest number of cases in these core coincided with the lowest human development index covering education, with the largest acreage of coffee (core Franca) and also as the largest area of cane sugar grown (core Barretos) in these locations, which in turn may indicate that the presence of labor, temporary labor in rural areas, combined with socioeconomic/cultural factors might contribute to the spread and establishment of bovine cysticercosis in these áreas.
Prevalence, spatial distribution and risk factors for cattle cysticercosis in the state of São Paulo, Brazil
Keywords: Bovine cysticercosis; Cysticercus bovis; Georeferencing; Taenia saginata